FORMULATION OF BASIL (OCIMUM BASILICUM) LEAF EXTRACT AS ANTISEPTIC POWDER AND TESTS OF INHIBITORY POWER AGAINST STAPHYLOCOCCUS AUREUS - Tatik Handayani; Susilowati Andari (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2023)
Basil is a plant that grows wild in the yard. The citral content in this plant produces a distinctive aroma. Utilization of this plant in general is still limited to consumption as fresh vegetables or certain traditional dishes. Basil leaves contain many useful compounds for the body such as vitamins A, B, C, beta-carotene, minerals, proteins, carbohydrates, fats, flavonoids, arginine, anetol and boron. Research on the use of basil leaf extract has been shown to have an effect on reducing the number of Staphylococcus Aureus bacteria, microorganisms that are pathogenic.The metod of vresearch is Experimental method , The sampling use a pupposive sampling,This research aims to make loose powder formulations using ethanol extract of basil leaves and test them for their inhibitory effect on Staphylococcus Aureus bacteria. The formulations made in this study were tabor powder with the main content of 1%, 2% and 3% basil leaf ethanol extract which then tested the of Staphylococcus Aureus. Based on the results of the study, the three formulations above each had an inhibitory power against Staphylococcus Aureus bacteria based on the research results, the three formulations above each had an inhibitory power against Staphylococcus Aureus bacteria Based on physical testing, both formulas 1, 2 and 3 showed results that met the requirements on organoleptic examination, pH, irritation properties, degree of fineness, pouring volume test and shock test, adhesion test and moisture test during storage for 2 weeks. From the results in this study it was concluded that the formulation above met the requirements.